Ecologia e biologia populacional do camarão hermafrodita protândrico simultâneo Exhippolysmata oplophoroides (Holthuis, 1948) (Caridea: Alpheoidea: Hippolytidae), na Costa Sudeste do Brasil - Venâncio, Marciano Antônio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The shrimp Exhippolysmata oplophoroides is a common species in the Southeast of Brazil, with no business interest and it is part of by-catch. The objective of this study is to characterize the ecological distribution and estimate the fecundity and the reproductive investment of E. oplophoroides in the southeast Brazilian coast. Individuals collected in the regions of Ubatuba and Caraguatatuba from July 2001 to June 2003 were used to study the ecological distribution, while individuals collected in Ubatuba in July 2011 were used to estimate fecundity and the reproductive investment. The samplings were carried out with an appropriated boat, equipped with double-rig trawls net. The length of the cephalothorax (CC) of the shrimp was measured under optic stereomicroscope. For the analysis of fecundity and investment, the CC of the individuals was measured using a Vernier caliper accuracy of 0.01 mm and grouped in size classes. The mass of the eggs was classified according to their development stage. A total of 4,059 individuals were collected. The Ubatuba region presented greater abundance than the region of Caraguatatuba, although it differed statistically (p = 0.1148). The most abundant were those of 5 and 20 meters (p = 0.0255). The highest abundance was of shrimp on FHO phase, followed by FHNO and FM, respectively. In relation to CC, no difference was observed between the sizes for the three demographic groups (p = 0.1733). The FM group was restricted to only the first four size classes (3.5 to 7.0 mm), indicating that as the individual grows it becomes (HPS). In the study of fecundity and reproductive investment a total of 116 individuals was analyzed, which ranged from 9.4 mm to 13.8 mm of CC. The average size of the individuals of the population was 11.77 ± 0.99 mm of CC. The results of simple linear regression showed a significant relationship between the length of the carapace and the number of eggs, for individuals with end-stage...

O camarão Exhippolysmata oplophoroides é uma espécie bastante comum no sudeste brasileiro, não possui interesse comercial sendo capturada como fauna acompanhante. O objetivo do estudo e caracterizar a distribuição ecológica e estimar a fecundidade e o investimento reprodutivo de E. oplophoroides no litoral sudeste brasileiro. Os indivíduos coletados nas regiões de Ubatuba e Caraguatatuba no período de julho de 2001 a junho de 2003, foram utilizados para estudar a distribuição ecológica, enquanto os indivíduos coletados em Ubatuba em julho de 2011 foram utilizados para estimar a fecundidade e investimento reprodutivo. As coletas utilizando um barco camaroneiro, equipado com redes de arrasto do tipo double-rig. O comprimento do cefalotórax (CC) dos camarões foi mensurado sob estereomicroscópio ópitico. Na análise de fecundidade e investimento os indivíduos tiveram o (CC) mensurado utilizando paquímetro de precisão 0.01 mm e agrupados clases de tamanho. A massa de ovos foi classificada de acordo com o seu estágio de desenvolvimento. Foram coletados 4059 indivíduos. A região de Ubatuba apresentou uma abundância maior do que a região de Caraguatatuba, embora não tenha diferido estatisticamente (p=0.1148). Os pontos mais abundantes foram os de 5 e 20 metros (p=0.0255). A maior abundância foi de camarões na fase FHO, seguido por FHNO e FM, respectivamente. Em relação ao (CC), não observou-se diferença entre os tamanhos para os três grupos demográfico (p= 0.1733). O grupo FM ficou restrito apenas às quatro primeiras classes de tamanho (3.5 a 7.0mm), indicando que a medida que o animal cresce ele passa a ser (HPS). No estudo de fecundidade e investimento reprodutivo foram analisadas um total de 116 individuos, que variaram 9.4 mm a 13.8 mm de CC. O tamanho médio dos indivíduos da população foi de 11.77 ± 0.99 mm de CC. Os resultados da regressão linear simples indicaram uma relação significativa entre o...
Keywords: Camarão; Hermafroditismo; Fecundidade; Recursos energeticos; Ecologia; Shrimps; Ecology